2015
DOI: 10.1007/s10995-015-1822-y
|View full text |Cite
|
Sign up to set email alerts
|

Reflections of Black Women Who Choose to Breastfeed: Influences, Challenges and Supports

Abstract: Black women such as our participants are critical partners as we develop systems of care to decrease disparities and increase Black women's successes in breastfeeding. Findings underscore the importance of having diverse, readily available, user-friendly, culturally sensitive options for Black women who choose to breastfeed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…19,[31][32][33]36 In addition, active inclusion of religious bodies as primary partners in BF promotion with the AA population should be included as part of cultural and sociological targeted interventions. 19,[31][32][33]36 Exemplars for these community-, state-, and tribal-level interventions targeting BF promotion for all women of diversity are supported by the national coalition of organizations, the United States Breastfeeding Committee (USBC). The USBC is committed to mitigating barriers by addressing the essential components of culturally competent BF care: consider Culture, show Respect, Assess/Affirm differences, show Sensitivity and Self-awareness, and do it all with Humility (CRASH).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,[31][32][33]36 In addition, active inclusion of religious bodies as primary partners in BF promotion with the AA population should be included as part of cultural and sociological targeted interventions. 19,[31][32][33]36 Exemplars for these community-, state-, and tribal-level interventions targeting BF promotion for all women of diversity are supported by the national coalition of organizations, the United States Breastfeeding Committee (USBC). The USBC is committed to mitigating barriers by addressing the essential components of culturally competent BF care: consider Culture, show Respect, Assess/Affirm differences, show Sensitivity and Self-awareness, and do it all with Humility (CRASH).…”
Section: Discussionmentioning
confidence: 99%
“…Families, peers, and community persistent support and encouragement for women boosted BF. 19,[31][32][33] The communal networks were instrumental for education, counseling, appraisal, interaction, engagement, successful transitions, positive deviance, reinforcement, and emotional well-being. 26,34,35 The AA women who breastfeed exhibit positive deviance.…”
Section: Theme One: Cultural Dimensionmentioning
confidence: 99%
“…Parents desired professional and individualized instruction regarding infant feeding that was in keeping with their attitudes, beliefs, culture, and feeding decision from various sources [83], including physicians, pediatric nurses, lactation consultants, or professionals working in health care centers or public nutrition programs, described collectively here as health care providers (HCP). In contrast, studies illuminated that many parents found "infant feeding advice, support, and education from their HCP inadequate, missing completely, inconsistent or contradictory" [36][37][38]41,42,44,46,[49][50][51]53,55,57,63,72,74,76,83,97,98,103,104]. As identified within some studies, while it is important to promote and maintain BF, it is also necessary to ensure that the care, education, and needs of parents and their infants that are not BF are met [74,76], without stigmatizing parents who do not BF [68].…”
Section: Parent's Expectations Of Education and Support Addressing Pementioning
confidence: 99%
“…2020, 10, x FOR PEER REVIEW 6 of 13 a desire for expanded infant nutrition education that included parent's wider community such as family members, rather than only mothers, was identified within some studies [67,79,80,105]. Role models and support groups were noted as important by parents, but perceived as inadequate [38,72,103].…”
Section: Parent's Expectations Of Education and Support Addressing Pementioning
confidence: 99%
“…The association we identified between more positive breastfeeding beliefs (per total score and each subscale score) and breastfeeding initiation/longer duration mirror prior findings in the literature suggesting the importance of positive beliefs about breastfeeding in improving breastfeeding rates (Brockway et al, 2017; Brown, 2014). While breastfeeding educational campaigns have done much to create more positive breastfeeding beliefs, we still lack a complete understanding of how cultural factors influence breastfeeding beliefs (Kamoun & Spatz, 2018; Lutenbacher, Karp, & Moore, 2016; Savage, Neshteruk, Balantekin, & Birch, 2016). Connecting cultural expectations to breastfeeding beliefs will help educators and clinicians understand how to emphasize the positive aspects of breastfeeding without undermining cultural traditions in diverse populations.…”
Section: Discussionmentioning
confidence: 99%